Inovasi Produk dan Kualitas Premium: Pola Pembelian Pangan Digital di Perum Bulog Parepare - Modding, Basri; Tijjang, Bakhtiar; putra, Pandi (Program Studi Manajemen Keuangan Syariah IAIN Parepare, 2025)
In the increasingly rapid digital era, this study reveals the key factors that drive digital food purchasing decisions at Perum Bulog Parepare, with a focus on product innovation and premium quality. Through quantitative analysis of consumer questionnaire data, this study identifies five important elements that influence buyer preferences: ease of use of digital platforms, superior product quality, competitive prices, attractive product innovations, and consumer trust. The findings show that consumers increasingly value seamless shopping experiences and high-quality products in the digital food ecosystem, with consumer trust acting as a catalyst in mitigating risk perceptions related to online transactions. The results of this study provide valuable insights for Perum Bulog Parepare to design effective strategies to face digital transformation, optimize platforms, improve product quality, and create relevant innovations. This study not only offers practical guidance for Bulog, but also contributes significantly to the understanding of the dynamics of the digital food market in Indonesia, becoming a valuable reference for industry players and policy makers in this sector.